Double side friction stir welding effect on mechanical properties and corrosion rate of aluminum alloy AA6061. Issue 2 (February 2023) - Priyasudana, Danang; Crisdion, Simonne Andrean; Puspitasari, Poppy; Triyono,; Jamasri,; Andoko,; Pramono, Diki Dwi
Abstract: Friction Stir Welding (FSW) is a solid-state welding method that has diffusion and different metal structures can blend well. Friction stir welding (FSW) has a weakness, one of which is the lack of flexibility the welding process is only carried out on one side of the plate being welded, so it is not applied on thick materials. Double side friction stir welding is a double working process in which the plate to be welded is subjected to friction from two tools on opposite sides. In the DS-FSW welding process, the dimensions and geometry of the tool and pin greatly affect the quality of the joint. This study to determine the mechanical properties and corrosion rate of Double side friction stir welding aluminum 6061 with variation rotation speed and axis of top and bottom tools. The results of this radiographic test can be seen that specimen 4 welded with variations in speed and tool position has defects in the form of incomplete fusion (IF). The results of microstructural observations showed that the heat caused by the welding process resulted in recrystallization in the form of fine grains in the stirring area and there was no phase change. The highest hardness value in the welding area is specimen B. The largest bending value at the 1G welding positions is specimen D, which is 41.86 MPa with a strain value of 13.23%, while the smallest value at the 4G welding position is specimen A, which is 38.18 MPa with a strain value of 5.03%. The fracture and crack surfaces showed that crack initiation, propagation and material stirring failure occurred in all test specimens, even though the impact test specimen was cut in a small area of Incomplete Fusion, but the test results showed that there was still a surface of the parent metal that had not been stirred. The corrosion test method uses three electrode cells with corrosion media as a substitute for seawater with a salinity of 3.5% NaCl, result of corrosion test is specimen B at the 1G welding position has the highest corrosion rate value of 0.63856 mm/year and specimen An at the 1G welding position has the lowest corrosion rate of 0.058567 mm/year.